UPAYA REHABILITASI EKOSISTEM TERUMBU KARANG TERDAMPAK TUMPAHAN MINYAK DI DESA FAEKHUNA, KECAMATAN AFULU, KABUPATEN NIAS UTARA - Hilal Idama Dalimunthe; Hasbi Husaini; Vindy Rilani Manurung; Muhammad Azis Yudhiwinata; Machmul Prayudi Harahap; Muhammad Adam Pahlevy; Muhammad Najhan Adisusilo; Muhammad Fahmi Abdillah; Abdullah Hanif; Stefany Florencia; Hana Sazida; Daniel Tambunan; Muhammad Thariq Abshar; Ferdiansyah Manurung; Bina Kristian Waruwu (Universitas Mataram, 2023)
Faekhuna'a Village is one of the villages affected by asphalt oil spills. The oil spillage that has polluted the waters has led to a decline in the income of fishermen, due to the damage to coral reefs. To address this problem, direct implementation of the